2018
DOI: 10.3390/w10070953
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Analysis of Macrophytes Role in the Flow Distribution in the Anastomosing River System

Abstract: Abstract:The impact of vegetation on the hydrology and geomorphology of aquatic ecosystems has been studied intensively in recent years. Numerous hydraulic models developed to date help to understand and quantitatively assess the influence of in-stream macrophytes on a channel's hydraulic conditions. However, special focus is placed on single-thread rivers, leaving anastomosing rivers practically uninvestigated. To fill this gap, the objective of this study was to investigate the impact of vegetation on flow d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 74 publications
0
12
0
1
Order By: Relevance
“…Macrophytes, as a vital component of aquatic ecosystems, are among the groups of organisms considered by the WFD for river assessment. Plants are sensitive indicators of the aquatic environment, able to detect eutrophication [2,[5][6][7][8][9], and to some extent also acidification [10], water flow [11], and morphological degradation [8]. Furthermore, aquatic plants respond to various other environmental factors, including light, temperature, and substrate [12].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophytes, as a vital component of aquatic ecosystems, are among the groups of organisms considered by the WFD for river assessment. Plants are sensitive indicators of the aquatic environment, able to detect eutrophication [2,[5][6][7][8][9], and to some extent also acidification [10], water flow [11], and morphological degradation [8]. Furthermore, aquatic plants respond to various other environmental factors, including light, temperature, and substrate [12].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many issues related to restoration, flood protection, and the functioning of aquatic ecosystems in natural river valleys are solved using hydrodynamic flow models [1][2][3][4][5]. In most cases, terrain features are being represented using Digital Terrain Models (DTM), allowing a combination of different sources of spatial data.…”
Section: Introductionmentioning
confidence: 99%
“…In still scarce studies where flood routing is analyzed with the use of vegetationroughness models, some researchers tend to consider plant properties to be model parameters that should be calibrated, i.e., identified with respect to observations. So, treating them similarly to Manning coefficients, which are usually obtained by the model calibration, where their values are adjusted, ensures an agreement between computed and observed, e.g., water levels, stream velocities, or flow rates -by solving the inverse problem (e.g., Khatibi et al, 1997;Marcinkowski et al, 2018Marcinkowski et al, , 2019Yu et al, 2019). The example is given by Dalledonne et al (2019), who identified vegetation parameters describing, e.g., stem diameters, their heights, drag coefficients, and a leaf area index in the two-dimensional flow model.…”
Section: Introductionmentioning
confidence: 99%